No effect on functional outcome after repair of pronator quadratus in volar plating of distal radial fractures: a randomized clinical trial. (November 2019) - Sonntag, Jesper; Woythal, Linn; Rasmussen, Per; Branner, Ulrik; Hølmer, Per; Jensen, Andreas Kryger; Lange, Kai H. W.; Brorson, Stig
Abstract : Aims: The aim of this study was to investigate the difference in functional outcome after repair and non-repair of the pronator quadratus muscle in patients undergoing surgical treatment for a distal radial fracture with volar plating. Patients and Methods: A total of 72 patients with a distal radial fracture were included in this randomized clinical trial. They were allocated to have the pronator quadratus muscle repaired or not, after volar locked plating of a distal radial fracture. The patients, the assessor, the primary investigator, and the statistician were blinded to the allocation. Randomization was irreversibly performed using a web application that guaranteed a secure and tamper-free assignment. The primary outcome measure was the Patient Rated Wrist Evaluation (PRWE) after 12 months. Secondary outcomes included the Disabilities of the Arm, Shoulder and Hand (DASH) score, pronation strength, grip strength, the range of pronation and supination, complications, and the operating time. Results: Of the 72 patients, 63 (87.5%) completed follow-up for the primary outcome measure: 31 (86.1%) from the non-repair group and 32 (88.9%) from the repair group. At the 12-month follow-up, the mean difference in PRWE of 5.47 (95% confidence interval (CI) -4.02 to 14.96) between the repair (mean 18.38 (95% CI 10.34 to 26.41)) and non-repair group (mean 12.90 (95% CI 7.55 to 18.25)) was not statistically significant (p = 0.253). There was a statistically significant difference between pronation strength, favouring non-repair. We found no difference in the other secondary outcomes. Conclusion: We found that repairing pronator quadratus made no difference to the clinical outcome, 12 months after volar plating of a distal radial fracture. We conclude that there is no functional advantage in repairing this muscle under these circumstances and advise against it. Cite this article: Bone Joint J 2019;101-B:1498–1505